2011
DOI: 10.1016/j.neuropsychologia.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of lateral anterior temporal lobe and inferior parietal lobule in coding function and manipulation tool knowledge: Evidence from an rTMS study

Abstract: A remarkable cognitive ability in humans is the competency to use a wide variety of different tools. Two cortical regions, the anterior temporal lobes (ATL) and left inferior parietal lobule (IPL), have been proposed to make differential contributions to two kinds of knowledge about tools - function vs. manipulation. We used repetitive transcranial magnetic stimulation (rTMS) and two semantic decision tasks to assess the role of these regions in healthy participants. Participants made semantic decisions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
84
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 60 publications
15
84
0
1
Order By: Relevance
“…Finally, these findings converge with two recent studies that used transcranial magnetic stimulation to show that, for both photographs of objects (Pobric et al, 2010) and object-words (Ishibashi et al, 2011), a region of the left IPL participates in the representation of the manipulability of the object-that is, how it is used-while a region of the left aTC contains more abstract, modality-nonspecific information about object function-that is, why it is used (see also Canessa et al, 2008). These regions correspond well with the left IPL and left aTC regions observed to be associated with representing action implementation ("how") and motive ("why"), respectively, in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, these findings converge with two recent studies that used transcranial magnetic stimulation to show that, for both photographs of objects (Pobric et al, 2010) and object-words (Ishibashi et al, 2011), a region of the left IPL participates in the representation of the manipulability of the object-that is, how it is used-while a region of the left aTC contains more abstract, modality-nonspecific information about object function-that is, why it is used (see also Canessa et al, 2008). These regions correspond well with the left IPL and left aTC regions observed to be associated with representing action implementation ("how") and motive ("why"), respectively, in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, errors in the perception of object manipulation can occur after damage external to left IPL, suggesting that the ventro-dorsal stream can be indirectly disturbed by disrupting communication at different parts of the pathway. These findings support previous research confirming that lesions implicating the left IPL can give rise to apraxia and result in impaired perception of object-use manipulation Daprati & Sirigu, 2006;Buxbaum et al, 2007;Goldenberg 2009;Ishibashi et al, 2011). They also suggest that apraxia may be associated with deficits in motor imagery, which in turn compromise the integration of known and visual object properties.…”
Section: * Discussionsupporting
confidence: 90%
“…Using repetitive transcranial magnetic stimulation (rTMS), stimulation of the left IPL slows object manipulation judgements whereas anterior temporal lobe stimulation slows function judgements (Ishibashi, Lambon Ralph, Saito, & Pobric, 2011). The perception of object function appears to be attributed to more ventral and semantic systems (Hodges, Bozeat, Lambon Ralph, Patterson, & Spatt, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that HF rTMS to the right DLPFC increased RT selectively during the decision phase, demonstrating the roles of the PPC and the DLPFC in the delay and decision phases related to spatial working memory. In a study on the lateral anterior temporal lobe (ATL) and the inferior parietal lobule (IPL) in coding function (what for) and manipulation (how) of tools [33], LF rTMS to lateral ATL increased RT for the "function" judgments, whereas LF rTMS of IPL increased RT for the "manipulation" judgments. Gongora et al [25] conducted a visuomotor task using LF rTMS and quantitative electroencephalography.…”
Section: Decision-makingmentioning
confidence: 99%
“…In decision-making studies relevant to cognitive functions, rTMS affects visuospatial attention [71], perception [57], object identification [77], spatial working memory [36], function and manipulation tool knowledge [33], and visuomotor tasks [25].…”
Section: Decision-makingmentioning
confidence: 99%